FIELD TRIALS ON CULTURE OF CLARIAS BATRACHUS - VENKATESHVARAN, K.; LANDGE, ASHA T.; VENUGOPAL, G. (Journal of Indian Fisheries Association, 2015)
Culture of Magur, Clarias batrachus on an experimental basis was carried out for a totalof 159 days in 6 earthen ponds each of 0.02 ha in area, singly in 2 ponds and in combination withRohu, Labeo rohita in 4 ponds. Three different artificial feeds were used. Growth of Magurvaried from 89 to 110 and survival form 93 to 100%. Out of the 3 feeds used, feed formulation2 yielded better results. Length-weight relationship parameters were found as log W =0.4979067 + 1.878346 log L; - 1.1116438 + 2.3511497 log L; and -1.238157 + 2.433125 log Lindicating growth to be not isometric. Relative condition factor (K u) was close to.or higher than1.0 only in fishes higher than 200 mm of total length; K. values which were less than 1.0 uptoJanuary, reached values greater than 1.0 by March-April. Condition appears to be influencedby spawning rather than feeding.